2003
DOI: 10.1101/gad.1058103
|View full text |Cite
|
Sign up to set email alerts
|

The RAG1 N-terminal domain is an E3 ubiquitin ligase

Abstract: V(D)J recombination is a process through which DNA segments are cleaved, shuffled, and then religated to assemble functional immunoglobulin and T cell receptor loci. The process is required for the function of the adaptive immune response and provides a large degree of diversity needed by the antigen receptors. Recombination must also be highly regulated in terms of its DNA target specificity, developmental stage, and coordination with other nuclear events such as cell cycle. Undesired consequences of aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…Our interest in SUMOylation originated with the recognition that the E3 enzymes for this pathway frequently contain the RING motif. This protein structure is also common among the ubiquitin E3 enzymes and is found in the RAG1 protein important for V(D)J recombination (20,45,62). However, we do not have evidence of a functional link between this aspect of RAG1 and the SUMOylation of XRCC4 at this time.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Our interest in SUMOylation originated with the recognition that the E3 enzymes for this pathway frequently contain the RING motif. This protein structure is also common among the ubiquitin E3 enzymes and is found in the RAG1 protein important for V(D)J recombination (20,45,62). However, we do not have evidence of a functional link between this aspect of RAG1 and the SUMOylation of XRCC4 at this time.…”
Section: Discussionmentioning
confidence: 44%
“…Our previous finding of a ubiquitin ligase activity in RAG1 suggested that posttranslational peptide modifications may contribute to the regulation of V(D)J recombination (45,62). The recognition of covalent modification of a protein by the addition of a peptide modifier was first recognized for ubiquitylation (reviewed in references 39 and 60).…”
mentioning
confidence: 99%
“…Several other proteins involved in DNA repair or maintenance are also regulated by SUMO. Furthermore, the RING motif in RAG1 raises the possibility that ubiquitin or SUMO are involved in V(D)J recombination [12]. Here we report that raising the cellular level of SUMO or increasing the degree of protein SUMOylation stabilizes Ku70.…”
Section: Introductionmentioning
confidence: 63%
“…The RING domains of Rag1 and Rad5 are homologous to the Rad16 RING domain (Fig. 1A and B), and both Rag1 and Rad5 have E3 activity or are components of multisubunit E3 complexes (69,77). Thus, Rad16 is homologous to proteins with known E3 activity.…”
Section: Resultsmentioning
confidence: 99%